Necessity and Free Will in the Thought of Bardaisan of Edessa - Hegedus, Tim (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2003)
AbstractWe examine here how the Syrian philosopher and theologian Bardaisan conciliates necessary fate and free will in man. Our study is based on an examination of the Book of the Laws of Countries, a dialogue on free will and astral fate, featuring Bardaisan, a few of his disciples and an opponent.